Inventive Multi-Issue Negotiation: A TRIZ-Aided Behavioral Approach with the Wolf Game and Modified Even-Swaps - Altun, Koray (Springer, 2025)
Negotiation in complex multi-issue scenarios requires a structured and adaptive approach that balances conflicting priorities while incorporating behavioral dynamics. Traditional decision-making models often assume that predefined alternatives are available, which does not reflect real-world negotiation complexities. This study introduces the Wolf Game Negotiation Model (WGNM), an inventive negotiation framework that integrates TRIZ-based inventive principles (IPs) with behavioral adaptation strategies. WGNM constructs negotiation pathways dynamically by leveraging psychological positioning (IP13), segmentation (IP1) resource utilization (IP25), and tactical adaptation (IP21) to refine decision alternatives in real-time. Unlike static compromise-based models, WGNM enables iterative trade-off adjustments, allowing negotiators to systematically manage concessions while maintaining strategic control. The study also examines the integration of Modified Even-Swaps Mechanism (MESM) with WGNM, demonstrating their complementary strengths in decision structuring and adaptive negotiation. A case study in the injection molding industry illustrates how WGNM enhances negotiation efficiency by bridging the gap between decision support methodologies and behavioral negotiation models. The findings highlight the importance of inventive problem-solving in dynamic negotiations, leading to superior outcomes in cost, efficiency, and long-term strategic collaboration.
Keywords: Behavioral decision-making; Multi-issue negotiation; TRIZ; Wolf game; Inventive principles (IPs)